Clinical presentation and etiology of Cushing's syndrome: Data from ERCUSYN. (18th August 2022) - Valassi, Elena
Abstract: This review presents the data on clinical presentation at diagnosis in 1564 patients included in the European Registry on Cushing's syndrome (ERCUSYN), of whom 1045 (67%) had pituitary‐dependent Cushing's syndrome (CS) (PIT‐CS), 385 (25%) had adrenal dependent CS (ADR‐CS) and 89 (5%) had ectopic adrenocorticotropic hormone syndrome (ECT‐CS). The most frequent symptoms in the overall series were weight gain (83%), hypertension (79%), skin alterations (76%) and myopathy (70%). Diabetes mellitus was present in 32% and depression in 35% of patients. Skin alterations, menstrual irregularities and reduced libido were more prevalent in PIT‐CS patients compared to ADR‐CS patients, whereas patients with ECT‐CS more frequently had diabetes mellitus, myopathy, hirsutism and vertebral fractures compared to the other etiologies, consistent with a more severe clinical scenario. Reduced libido and bone fractures were more prevalent in men compared to women. Quality of life was poor at diagnosis, irrespective of the etiology of CS, and also associated with the presence of depression at baseline. A delay of 2 years between the onset of symptoms and diagnosis was also observed, with a high number of specialists consulted, who often missed the correct diagnosis. To develop strategies aimed at shortening the time elapsed to diagnosis, it is important to rapidly start treatment and reduce the burden of the disease on patient psychophysical health and longevity.